2013
DOI: 10.1121/1.4794382
|View full text |Cite
|
Sign up to set email alerts
|

Input/output functions of different-latency components of transient-evoked and stimulus-frequency otoacoustic emissions

Abstract: The input/output functions of the different-latency components of human transient-evoked and stimulus-frequency otoacoustic emissions are analyzed, with the goal of relating them to the underlying nonlinear dynamical properties of the basilar membrane response. Several cochlear models predict a cubic nonlinearity that would yield a correspondent compressive response. The otoacoustic response comes from different generation mechanisms, each characterized by a particular relation between local basilar membrane d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 39 publications
7
58
1
Order By: Relevance
“…As such, the generalization of the findings to other frequencies is unclear. Similar temporal spacing between different-latency components and growth rates to those reported in the current study have been observed at frequencies through 8 kHz (e.g., Goodman et al 2009 andSisto et al 2013) and demonstrate that the phenomenon of different-latency components is not unique to the 2 kHz TEOAE. SL components have also been measured for TEOAE frequencies between 1 and 1.5 kHz (e.g., Goodman et al 2009;Moleti et al 2012), which is closer to the transition frequency between basal and apical mechanics (Shera et al 2010;Dhar et al 2011).…”
Section: Generalization To Other Teoae Frequenciessupporting
confidence: 87%
See 2 more Smart Citations
“…As such, the generalization of the findings to other frequencies is unclear. Similar temporal spacing between different-latency components and growth rates to those reported in the current study have been observed at frequencies through 8 kHz (e.g., Goodman et al 2009 andSisto et al 2013) and demonstrate that the phenomenon of different-latency components is not unique to the 2 kHz TEOAE. SL components have also been measured for TEOAE frequencies between 1 and 1.5 kHz (e.g., Goodman et al 2009;Moleti et al 2012), which is closer to the transition frequency between basal and apical mechanics (Shera et al 2010;Dhar et al 2011).…”
Section: Generalization To Other Teoae Frequenciessupporting
confidence: 87%
“…The current study extended previous work that has reported on the growth rates and latencies of different-latency TEOAE components (e.g., Goodman et al 2009;Sisto et al 2013) by examining the relationship between each component's latency and the suppressor frequency that caused the greatest change in the component's magnitude. This relationship was of interest as it provides an empirical test of the hypothesis that shorter-latency components are generated basal to longer-latency components of similar frequency (Withnell et al 2008;Goodman et al 2011;Moleti et al 2013).…”
Section: Basal Contributions To Sl Teoae Componentssupporting
confidence: 51%
See 1 more Smart Citation
“…Suppression patterns, noise-exposure experiments, component decomposition analysis and correlations between OAEs and hearing threshold suggest that SFOAEs, transient-evoked (TE) OAEs, and distortion-product (DP) OAEs in humans and several laboratory species may have an extended generation region (e.g. Sutton 1985;Guinan 1990;Avan et al 1993Avan et al , 1995Avan et al , 1997Withnell et al 2000;Harding et al 2002;Ellison and Keefe 2005;Dreisbach et al 2008;Martin et al 2009Martin et al , 2010Charaziak et al 2013;Sisto et al 2013). …”
Section: Extended Region Of Sfoae Generation At Low Frequenciesmentioning
confidence: 99%
“…Recently, it has been demonstrated that significant SFOAE generation may occur slightly basally to the resonant region, within 1-2 mm in humans, corresponding to a relative frequency shift of order 15-30 % (e.g., Moleti et al 2013). Such nearbasal sources should correspond to the short-latency OAE components observed in humans (e.g., Sisto et al 2013). Significant delay differences are associated indeed to short spatial differences in the hightuning, sensitive human cochlea.…”
Section: Introductionmentioning
confidence: 99%